In Silico Study of Organo-selenium with PPAR-γ and NF-κB Receptors for Cardiovascular Protection - Ayu Shalihat; Cecep Suhandi; Aliya Nur Hasanah; Mutakin Mutakin (Jurnal Kimia Sains dan Aplikasi, 2026)
Cardiovascular disease (CVD) continues to represent a significant global health challenge, leading to the need for new and more effective therapeutic approaches. Organo-selenium compounds have potential as antioxidants and anti-inflammatory agents, which may help protect the heart and vascular system. However, the molecular mechanisms by which Organo-selenium exerts its cardioprotective effects are still not fully understood. The interaction with key regulatory pathways such as peroxisome proliferator-activated receptor gamma (PPAR-γ) and nuclear factor kappa B (NF-κB) has not been clearly defined. Therefore, this study aims to investigate the molecular interactions between organo-selenium compounds and the PPAR-γ and NF-κB-inducing kinase receptors in the context of cardiovascular protection. Molecular docking simulations were performed using the ligand-binding domain of PPAR-γ and the 20 organo-selenium ligands. The binding affinities and interactions between organo-selenium and receptors were analyzed. Among the screened organo-selenium ligands, compound 13 exhibited the most favorable binding affinity toward both PPAR-γ and NF-κB compared to the native ligand. Based on these results, compound 13 was selected for molecular dynamics simulations. The molecular dynamics study, using parameters such as RMSD, RMSF, SASA, and the Gyration plot, shows that compound 13 with PPAR-γ exhibits better stability and flexibility. At the same time, the NF-κB interaction, though stable, may be less energetically favorable than the native ligand. These interactions suggest that compound 13 (Ebselen) may modulate PPAR-γ activity, thereby influencing cell signaling pathways involved in cardiac protection. Overall, the findings suggest that modulation of the PPAR-γ pathway by compound 13 may represent a promising mechanism in cell signaling for cardiovascular protection.